Air Traffic Flow Management by Ground Delay Program Measurement to Improve Airline Operational Efficiency - สังข์ทอง ดุษฎี (KBU Journal of Aviation Management:KBUJAM, 2023)
Objective of this research are 1) to study the air traffic flow management by ground delay program measure 2) to study the airlines operational efficiency with the ground delay program Measure by pilots who operated in and out airports concerned. The data were collected by using questionnaires completed by 400 pilots who operated for airline operators. Data analysis employed frequency, arithmetic mean (x̄), percentage and standard deviation. The study presented the following results: 1) The airline operational efficiency improvement with the agreement level of Pilot-in-Command (PIC) and Co-Pilot were at the high level with no statistically significant difference. 2) The airline operational efficiency improvement with the agreement level of pilots who have an experience in operating flights in and out of European countries and pilots who don’t have this experience were at the high level with no statistically significant difference. 3) The airline operational efficiency improvement with the agreement level of pilots with experienced in operating intercontinental flight and pilots without this experience were at the high level with no statistically significant difference. The suggestion for extended from this research is, the Air Traffic Flow Management (ATFM) authority should increase the communication channels with relevant parties for correct knowledge and understanding in Ground Delay Program. Airlines operations unit should take in to account and emphasize the Air Traffic Flow Management (ATFM) by conduct a training regarding Air Traffic Flow Management (ATFM) to the operations member concerned and make sure that all relevant parties understand and operate correctly. Further studies may be expanding population group who is a Flight Operations Officer or related duty. Study the use of Ground Delay Program at other area of operations such as Reporting Point in the airspace or route to improve the Air Traffic Flow Management (ATFM) measures.